Structure and chemistry of crankcase and exhaust soot extracted from diesel engines. (July 2016) - Sharma, Vibhu; Uy, Dairene; Gangopadhyay, Arup; O'Neill, Ann; Paxton, William A.; Sammut, Alex; Ford, Monica A.; Aswath, Pranesh B.
Abstract: Carbonaceous structure and chemical composition of diesel soot extracted from crankcase oil as well as soot taken from the exhaust have been investigated. Visible Raman spectroscopy indicated a higher degree of graphitization and smaller ionic impurities in the exhaust soot compared to crankcase soot and UV Raman indicated the presence of (CO3 ) 2− and (PO4 ) 3− in crankcase soot. Changes in the chemistry of the carbonaceous soot particles are due to its interaction with the lubricant in the crankcase and tribological contacts in the engine. HR-TEM images suggest turbostratic structure in soot agglomerates and nano-crystalline species embedded in crankcase soot while exhaust soot only showed turbostratic structure. EDS coupled with HR-TEM exhibited P, S, O, Ca and Zn in crankcase soot while the exhaust soot only exhibits C and O. Lattice spacing measurement suggests the possible composition of the nano-crystallites are phosphates, sulfates and oxides of Ca, Zn and Fe. XRD results revealed the crystalline species in soot extracted from crankcase oil are Ca2 (SO4 )2 (H2 O) (Bassanite) and Zn4 (PO4 )2 (OH)2 (H2 O)3 (Spencerite). XANES analysis indicates the presence of ZnSO4, ZnS, FeSO4 along with CaSO4 and Ca3 (PO4 )2 as possible compounds that arise from interaction of the detergent chemistry with tribological surfaces.